TRANSFORMASI SISTEM INFORMASI MANAJEMEN SEKOLAH (SIMS): EFEKTIVITAS, TANTANGAN, DAN SOLUSI DI MASA KINI - Hamid, A.; Aslan, Aslan (CV. Lafadz Jaya, 2025)
The transformation of the School Management Information System (SIMS) is a strategic step in modernising education governance in the digital age. This article discusses the effectiveness, challenges, and solutions for implementing SIMS through a literature review. The results of the study indicate that SIMS can improve administrative efficiency, data accuracy, and transparency in education services. However, this transformation process still faces various obstacles, such as infrastructure limitations, low digital literacy, resistance to change, and data security issues. To optimise the benefits of SIMS, comprehensive solutions are needed in the form of infrastructure strengthening, digital literacy training, adaptive system development, and sustainable policy support. With this approach, SIMS can become a key pillar in realising effective and responsive school governance in the present day.